ETHICAL IMPLICATIONS OF ARTIFICIAL INTELLIGENCE: AN ISLAMIC PERSPECTIVE - Dr. Khanzada Muhammad Waqar; Muhammad Ibrahim; Dr. Mufti Muhammad Iltimas Khan* (Journal of Religion and Society, 2025)
The rapid advancement of Artificial Intelligence (AI) has raised significant ethical concerns, particularly from an Islamic perspective, where morality, justice, and social responsibility are integral to decision-making. This paper explores the ethical implications of AI within the framework of Islamic teachings, emphasizing key concepts such as accountability (mas'ūliyya), justice (ʿadl), and the sanctity of human dignity. It examines how AI-driven technologies intersect with Islamic moral values and the potential consequences of their application in various sectors, including finance, healthcare, and governance. The study highlights the challenges posed by AI, including bias, privacy concerns, and the displacement of human agency, while advocating for an ethical framework rooted in Islamic principles. By integrating Shariah-compliant guidelines into AI development, this research proposes a balanced approach that ensures technological progress aligns with human welfare and ethical integrity. The paper concludes with recommendations for Muslim scholars, policymakers, and AI developers to collaborate in shaping AI systems that uphold Islamic ethical standards while fostering innovation. Keywords: Artificial Intelligence, Islamic Ethics, Ai Governance, Accountability, Justice, Privacy, Shariah Compliance, Moral Responsibility, Ethical Ai, Human Dignity.